Show & tell : how everybody can make extraordinary presentations - Roam, Dan (Portfolio/Penguin, 2014)
" "If I tell you the truth, if I tell it with a story, and if I tell that story with pictures, I can keep you glued to your seat. Let me show you how." For the vast majority of us, giving a presentation is an extremely difficult and nerve-wracking process, whether we're in a one-on-one meeting, a conference room with a dozen strangers, or a lecture hall in front of thousands. But according to Dan Roam, the visual communications expert and acclaimed author of The Back of the Napkin, it doesn't have to be so hard. We struggle when we forget the basic steps we learned in kindergarten: show and tell. In this short but powerful book, Roam introduces a new set of tools for making extraordinary presentations in any setting. He also draws on ideas he's been honing for more than two decades, as an award-winning presenter who has brought his whiteboard everywhere from Fortune 500 companies to tiny startups to the White House. Even if you're already a good speaker, you'll learn more about understanding your audience, organizing your content, building a clear storyline, creating effective visuals, and channeling your fear into fun. And you'll master three fundamental rules: When we tell the truth, we connect with our audience, we become passionate, and we find self-confidence. When we tell a story, we make complex concepts clear, we make ideas unforgettable, and we include everyone. When we use pictures, people see exactly what we mean, we captivate our audience's mind, and we banish boredom. From nailing the opening to leaving a lasting impression, you'll soon be able to give the performance of a lifetime, time after time. "--